2009
DOI: 10.1111/j.1365-2230.2008.03050.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of chickenpox in young South Korean soldiers and correlation with atopic dermatitis

Abstract: In this population-based study, the epidemiological trend of chickenpox and AD over a period of 3 years within the military personnel of South Korea is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Consistent with other areas of China, two peaks of varicella incidence were detected in Jinan: the major peak occurred in November–January, and a minor one in April–May. A similar situation was also observed in Korea [ 6 ], located in the same climate zone as Jinan. However, in southern Japan, which has a subtropical monsoon climate, the incidence of varicella was highest in August and lowest in winter [ 5 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with other areas of China, two peaks of varicella incidence were detected in Jinan: the major peak occurred in November–January, and a minor one in April–May. A similar situation was also observed in Korea [ 6 ], located in the same climate zone as Jinan. However, in southern Japan, which has a subtropical monsoon climate, the incidence of varicella was highest in August and lowest in winter [ 5 ].…”
Section: Discussionsupporting
confidence: 82%
“…Although routine childhood varicella vaccination has been strongly recommended by the government, the incidence of varicella in Jinan has reached a high level in recent years. In 2011, the annual incidence of varicella was 55 per 100,000, a substantially higher incidence rate than that of Japan (1.3 per 100,000) [ 5 ], Korea (35 per 100,000) [ 6 ] and Taiwan (32 per 100,000) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incidence peaked in January in Taiwan and in March and September in India [41,61]. In South Korea, the highest numbers of cases were reported in January and November and the lowest during August and September [51].…”
Section: Incidence and Number Of Cases Per Annummentioning
confidence: 99%
“…There were very limited data on complication rates in the general population. One Australian study of a pediatric varicella outbreak, one study in India in nursing students, and one study in South Korea in young soldiers, all reported no complications in their study populations [51,101,102]. A prospective study identified the children hospitalized with severe varicella following introduction of a one-dose varicella vaccination from 2005 [6].…”
Section: Complicationsmentioning
confidence: 99%